Computational Creativity in Slovenia - Pollak, Senja; Wiggins, Geraint A.; Žnidaršič, Martin; Lavrač, Nada (Informatica, 2018)
Computational Creativity is a field of Articial Intelligence that addresses processes that would be deemed creative if performed by a human. The field has been very active since 1999, and is now an established research field with its own International Conference on Computational Creativity (ICCC) conference series founded in 2010. This paper brifley surveys the field of Computational Creativity (CC) that is based on the analysis of ICCC conference papers, followed by a more detailed presentation of projects and selected contributions of Slovenian researchers to the field.